2007
DOI: 10.1007/s00586-007-0552-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for back pain-related loss of working time after surgery for lumbar disc herniation: a 5-year follow-up study

Abstract: The aim of this study is to explore the occurrence and the risk factors of back-related loss of working time in patients undergoing surgery for lumbar disc herniation. One hundred and fifty-two gainfully employed patients underwent surgery for lumbar disc herniation. Two months postoperatively, those patients completed a selfreport questionnaire including queries on back and leg pain (VAS), functional capacity (Oswestry disability index-ODI, version 1.0), and motivation to work. After 5 years, lost working tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 52 publications
5
43
0
2
Order By: Relevance
“…This study shows, in accordance with previous studies, that personal characteristics of the employee, such as having a positive attitude towards going back to work, and social support in the workplace (36,37) are promoting factors for RTW. Our findings are in line with a recent study that showed that positive working conditions, supportive workplace relationships, and work satisfaction are RTW facilitators following occupational injury (38).…”
Section: Interpreting Our Findingssupporting
confidence: 92%
“…This study shows, in accordance with previous studies, that personal characteristics of the employee, such as having a positive attitude towards going back to work, and social support in the workplace (36,37) are promoting factors for RTW. Our findings are in line with a recent study that showed that positive working conditions, supportive workplace relationships, and work satisfaction are RTW facilitators following occupational injury (38).…”
Section: Interpreting Our Findingssupporting
confidence: 92%
“…Since LDH disease became a sore point of the working population, there is a demand to set the risk factors for work disability days after concrete surgery, where the most predicting ODI [ 20, considerable degree of pain, poor motivation to work are among other confounding agents making the prognosis more complicated [44]. The early return to vigorous activities and daily work with the mean sick leave of 1.7 weeks seems likely not increasing the complication rate [8].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, lower ODI scores are associated with shorter work absence following lumbar disc herniation (Puolakka et al, 2008). For re-surgery, no related factors (age, gender, preoperative symptoms, physical activity, or employment) are previously defined; however, physiotherapy was not evaluated in that study (Häkkinen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%